Effects of Acetyl-L-Carnitine on Oxidative Stress in Amyotrophic Lateral Sclerosis Patients: Evaluation on Plasma Markers and Members of the Neurovascular Unit - Elena Grossini; Fabiola De Marchi; Sakthipriyan Venkatesan; Angelica Mele; Daniela Ferrante; Letizia Mazzini (MDPI AG, 2023)
Oxidative stress, the alteration of mitochondrial function, and the neurovascular unit (NVU), play a role in Amyotrophic Lateral Sclerosis (ALS) pathogenesis. We aimed to demonstrate the changes in the plasma redox system and nitric oxide (NO) in 32 new ALS-diagnosed patients in treatment with Acetyl-L-Carnitine (ALCAR) compared to healthy controls. We also evaluated the effects of plasma on human umbilical cord-derived endothelial vascular cells (HUVEC) and astrocytes. The analyses were performed at the baseline (T0), after three months (T1), and after six months (T2). In ALS patients at T0/T1, the plasma markers of lipid peroxidation, thiobarbituric acid reactive substances (TBARS) and 4-hydroxy nonenal (4-HNE) were higher, whereas the antioxidants, glutathione (GSH) and the glutathione peroxidase (GPx) activity were lower than in healthy controls. At T2, plasma TBARS and 4-HNE decreased, whereas plasma GSH and the GPx activity increased in ALS patients. As regards NO, the plasma levels were firmly lower at T0-T2 than those of healthy controls. Cell viability, and mitochondrial membrane potential in HUVEC/astrocytes treated with the plasma of ALS patients at T0-T2 were reduced, while the oxidant release increased. Those results, which confirmed the fundamental role of oxidative stress, mitochondrial function, and of the NVU in ALS pathogenesis, can have a double meaning, acting as disease markers at baseline and potential markers of drug effects in clinical practice and during clinical trials.